From Heaven to Earth : the reordering of Castilian society, 1150-1350 - Ruiz, Teofilo F., 1943- (Book collections on Project MUSE., 2004)
"Between the late twelfth century and the mid fourteenth, Castile saw a reordering of mental, spiritual, and physical space. Fresh ideas about sin and intercession coincided with new ways of representing the self and emerging perceptions of property as tangible. This radical shift in values or mentalites was most evident among certain social groups, including mercantile elites, affluent farmers, lower nobility, clerics, and literary figures - "middling sorts" whose outlooks and values were fast becoming normative." "Drawing on such primary documents as wills, legal codes, land transactions, litigation records, chronicles, and literary works, Teofilo Ruiz documents the transformation in how medieval Castilians thought about property and family at a time when economic innovations and an emerging mercantile sensibility were eroding the traditional relation between the two. He also identifies changes in how Castilians conceived of and acted on salvation and in the ways they related to their local communities and an emerging nation-state."--Jacket.